1991
DOI: 10.2307/3578060
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Three-Dimensional Radiation Dose Distributions Using MRI

Abstract: Recent investigations have shown that nuclear magnetic resonance (NMR) can be used in conjunction with a suitable chemical dosimeter to estimate the dose from ionizing radiation (Gore et al., Phys Med. Biol. 29, 1189-1197, 1984). Based on this fact it was proposed that spatial dose distributions can be measured in gels infused with the chemical dosimeter using NMR imaging. There have been few such attempts and they provided only qualitative results. In this paper, we report results demonstrating the feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
35
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 12 publications
7
35
2
Order By: Relevance
“…No significant diffusion of the ferric ions in the gel was found for up to 10 hours after irradiation by Prasad et al (1991). In contrast, investigations carried out by Schulz et al (1990) showed a diffusion coefficient of 1.58 ± 0.11 mm2 h-' for a concentration of 25 mM, and 1.83 ± 0.14 mm2 h-' for a concentration of 12.5 mM Sulphuric acid.…”
Section: Dosimetry For Modern Radiotherapymentioning
confidence: 65%
See 3 more Smart Citations
“…No significant diffusion of the ferric ions in the gel was found for up to 10 hours after irradiation by Prasad et al (1991). In contrast, investigations carried out by Schulz et al (1990) showed a diffusion coefficient of 1.58 ± 0.11 mm2 h-' for a concentration of 25 mM, and 1.83 ± 0.14 mm2 h-' for a concentration of 12.5 mM Sulphuric acid.…”
Section: Dosimetry For Modern Radiotherapymentioning
confidence: 65%
“…Their results showed an enhancement of about 4.5 in the measurement of the transverse relaxation rate and about 2.5 in the measurement of the longitudinal relaxation rate. In contrast to Prasad et al (1991), Gambarini et al (1994) found no significant enhancement by adding 1.5 mM and 3.5 mM benzoic acid with and without NaCl.…”
Section: Dosimetry For Modern Radiotherapymentioning
confidence: 74%
See 2 more Smart Citations
“…The use of a dosimeter gel, based on ferrous sulphate and agarose, and evaluated in a magnetic resonance (MR) scanner may eliminate some of these problems (4)(5)(6)(7)(8)(9). Other gel systems, based on a monomer solution, have been proposed (10).…”
mentioning
confidence: 99%